Stability analysis of partial differential variational inequalities in Banach spaces - Guo, Faming; Li, Wei; Xiao, Yi-bin; Migórski, Stanisław (Nonlinear Analysis: Modelling and Control, 2020)
In this paper, we study a class of partial differential variational inequalities. A general stability result for the partial differential variational inequality is provided in the case the perturbed parameters are involved in both the nonlinear mapping and the set of constraints. The main tools are theory of semigroups, theory of monotone operators, and variational inequality techniques.
Keywords: partial differential variational inequality; mild solution; stability; upper semicontinuity; continuity